BEBERAPA SIFAT FISIS DAN KIMIA BRIKET ARANG DARI LIMBAH ARANG AKTIF - Gustan Pari; Djeni Hendra; Hartoyo Hartoyo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
The result of a study on briqueting charcoal from activated charcoal residue, prepared by using the hydraulic press process is presented in this paper. The residue : was subjected to two different treatments, namely unwashed and washed with water. Following the treatment, each residue material was mixed with starch adhesive, using four different concentrations: 0 percent, 1 percent, 2 percent and 3 percent, consecutively.The respons evaluated from the briquetted charcoal are the moisture content, ash content, volatile matter, fixed carbon, density, crushing strength and calorific value. The result shows that moisture content ranges from 3,36 - 5,56 percent, ash content from 8,06 - 12,78 percent, volatile matter from 23,56 - 41,28 percent, fixed carbon from 45,9 - 68,38 percent, density from 0,6471-0,7985 gr/cm, crushing strength from 0,79 - 6,33 kg/cm and the calorific values ranged from 5243,25 - 6378,84 cal/gr.